Penerapan Aromaterapi Lavender untuk Mengatasi Masalah Utama Nyeri Akut pada Pasien Paska Open Reduction Internal Fixation (ORIF) - Novida Prima Wijayanti; Ida Rianawaty; Kurniawan Bagus Sugiarto; Rizka Choirunnisa (Akademi Keperawatan Karya Bhakti Nusantara, Magelang, Indonesia, 2024)
Background: Open Reduction Internal Fixation (ORIF) is a surgical procedure to manipulate broken bone fragments or fractures so that they return to their original state. The impact after this procedure is that a person can feel acute pain. Acute pain after Open Reduction Internal Fixation (ORIF) can be controlled with pharmacological and non-pharmacological management. One non-pharmacological treatment involves administering lavender aromatherapy. Objective: To understand the description of Mr. D and Mr. S before and after doing lavender aromatherapy and knowing the application of lavender aromatherapy. Method: This research is a qualitative descriptive study with a case study strategy, using 2 respondents, namely patients who experienced pain after Open Reduction Internal Fixation (ORIF). The procedure was carried out for 2 days by administering lavender aromatherapy for 15 minutes which was divided into 2 stages, measuring the pain scale before and after the procedure. Results: Lavender aromatherapy can reduce the pain scale, namely Mr. D before the procedure experienced pain on a scale of 5 and after the procedure his pain decreased to a scale of 3 and Mr. S experienced pain scale 6 before the procedure and after the procedure the pain decreased to scale 3. Conclusion: Lavender aromatherapy is effective in reducing the pain scale which is also supported by the provision of analgesics. Keywords: Acute pain; Lavender aromatherapy; ORIF